Hunger and Public Action. - Drèze, Jean (Oxford University Press, 1991)
This book analyses the role of public action in solving the problem of hunger in the modern world and is divided into four parts: Hunger in the modern world, Famines, Undernutrition and deprivation, and Hunger and public action.